Certain classes of analytic functions defined by fractional q-calculus operator - Ravikumar N. (Acta Universitatis Sapientiae: Mathematica, 2018)
In this paper, the concept of fractional q-calculus and generalized Al-Oboudi differential operator defining certain classes of analytic functions in the open disc are used. The results investigated for these classes of functions include the coefficient estimates, inclusion relations, extreme points and some more properties.